BRIDGING THE FINTECH GENDER GAP: STRATEGIES FOR ENHANCING WOMEN'S ACCESS TO FINANCIAL SERVICES - Sudarmo Sudarmo; Adi Mursalin; Meiyanti Widyaningrum; Khasanah; Naiyun Untung Utama (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The fintech gender gap, characterized by a significant disparity in women's access and utilization of financial technology products and services, presents a critical challenge to achieving financial inclusion. This article explores strategies for bridging the fintech gender gap and enhancing women's access to financial services. Through a comprehensive review of existing literature, this study identifies key factors contributing to the gender gap in fintech adoption, including individual-level controls and country characteristics. The article proposes various strategies to address the gap based on these insights. These strategies include promoting digital literacy and financial Education among women, developing user-friendly fintech products tailored to their needs, fostering an inclusive fintech ecosystem, and strengthening policy and regulation to ensure gender equality. The article emphasizes the importance of collaboration between policymakers, financial institutions, and technology providers to implement these strategies effectively. Through the implementation of these measures, it is hoped that the fintech gender gap can be narrowed, thereby promoting financial inclusion and empowering women in the digital economy.